Mating‐based regulation and ligand binding of an odorant‐binding protein support the inverse sexual communication of the greater wax moth, Galleria mellonella (Lepidoptera: Pyralidae). Issue 3 (1st March 2020) - Lizana, P.; Machuca, J.; Larama, G.; Quiroz, A.; Mutis, A.; Venthur, H.
Abstract: In moths, sex pheromones play a key role in mate finding. These chemicals are transported in the antennae by odorant‐binding proteins (OBPs). Commonly, males encounter conspecific females; therefore, several OBPs are male‐biased. Less is known, however, about how the olfactory system of moths has evolved toward inverse sexual communication, ie where females seek males. Therefore, the objective of this study was to identify the profile of OBPs and their expression patterns in the bee hive pest, Galleria mellonella, a moth that uses inverse sexual communication. Here, OBP ‐related transcripts were identified by an RNA Sequencing (RNA‐Seq) approach and analysed through both Reverse Transcription Polymerase Chain Reaction (RT‐PCR) in different tissues and quantitative real‐time PCR for two states, virgin and postmating. Our results indicate that G. mellonella has 20 OBPs distributed amongst different tissues. Interestingly, 17 of the 20 OBPs were significantly down‐regulated after mating in females, whereas only OBP7 was up‐regulated. By contrast, 18 OBP transcripts were up‐regulated in males after mating. Additionally, binding assays and structural simulations showed general odorant‐binding protein 2 (GOBP2) was able to bind sex pheromone components and analogues. These findings suggest a possible role of OBPs, especially GOBPs, in the inverse sexual communication of G. mellonella, with gene expression regulated as a response to mating. Abstract : Mating‐based regulation of odorant‐binding protein‐related transcripts identified in Galleria mellonella females and males plus ligand binding of a general odorant‐binding protein, support inverse sexual communication at the molecular level.